2021
DOI: 10.14379/iodp.proc.385.101.2021
|View full text |Cite
|
Sign up to set email alerts
|

Expedition 385 summary

Abstract: Introduction 4 Background 7 Site summaries 40 Preliminary scientific assessment 45 References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 84 publications
1
43
0
Order By: Relevance
“…Site U1545 (proposed Site GUAYM-01B) is located at 27°38.2315′N, 111°53.3396′W, ~52 km northwest of the axial graben of the northern Guaymas Basin spreading segment (see Figure F1 in the Expedition 385 summary chapter [Teske et al, 2021b]). The primary objective for this site is shared with Site U1546, located just 1.1 km away (Figure F3).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Site U1545 (proposed Site GUAYM-01B) is located at 27°38.2315′N, 111°53.3396′W, ~52 km northwest of the axial graben of the northern Guaymas Basin spreading segment (see Figure F1 in the Expedition 385 summary chapter [Teske et al, 2021b]). The primary objective for this site is shared with Site U1546, located just 1.1 km away (Figure F3).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…For sites U1545C and U1546D, the original objective in terms of microbiology was to elucidate the impact of sill intrusion on microbial activity at sites with similar sediment composition, TOC content (scattering between 1 and 2.5%) and stratigraphy but different sill intrusion histories. During the expedition downhole, temperature measurements indicated that the sill located at Site U1546D had reached thermal equilibrium with the surrounding sediment (Teske et al, 2021), so there is no local heating effect at present. Both sites have relatively high SRR near the seafloor, with maxima of 5.1 and 48.5 nmol cm −3 d −1 and with minima above MQL of 0.2 and 0.4 pmol cm −3 d −1 for sites U1545C and U1546D, respectively (Figures 3A,B).…”
Section: Sulfate Reduction Rates At Sites U1545c and U1546dmentioning
confidence: 98%
“…One of the main objectives of the International Ocean Discovery Program (IODP) Expedition 385 (Guaymas Basin Tectonics and Biosphere) was the investigation of microbial communities and activity in the deep subseafloor biosphere of Guaymas Basin. Detailed drill site descriptions are given by Teske et al (2020Teske et al ( , 2021 (Table 1). Sites U1545C and U1546D have a similar stratigraphy since the distance between these two sites is only about 1.1 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During International Ocean Discovery Program (IODP) Expedition 385, eight sites were drilled in Guaymas Basin with the broad goal of unraveling the physical, chemical, and biological processes that regulate the cycling of sedimentary carbon in a region where extensive chemical, temperature, and lithologic gradients impact both biotic and abiotic processes that release and/or sequester carbon in the sediment (Teske et al, 2021a). Emplaced volcanic sills that originate at the spreading center significantly alter the host sediment and control hydrothermal circulation patterns in Guaymas Basin (Einsele et al, 1980).…”
Section: Introductionmentioning
confidence: 99%